Aging Effect on Rock Wettability Alteration - Mahmood, Ahmed J. (Journal of Petroleum Research and Studies, 2022)
One of the factors controlling fluid distribution in porous media is wettability, which is ranging from water-wet to oil wet. Wettability could be changed due to the long-time contact with hydrocarbon liquids. Wettability alteration resulting from the aging of core samples in hydrocarbon liquids becomes a widely used technique. The aging of Core samples from different locations in different types of liquids had been studied. The aging periods used in these studies range from hours to 110 days. In this work, synthetic core samples were aged for a period ranging from 205 to 824 days into two different hydrocarbon liquids (heavy crude from the East Baghdad oil field and gas oil). Results show that long time aging periods dramatically alter wettability; also, heavy crude oil alters wettability higher than that of light hydrocarbon.